L’agriculture biologique et les paradoxes de la reconnaissance - Richardson, Mary (Anthropologica, 2022)
Organic agriculture as practised now emerged out of a counter-cultural social movement that sought to question conventional agricultural practices and to develop more eco? logically sound ways of producing food. It has hence long been at the margins of dominant agricultural models and has bene? fited poorly from formal support. Indeed, for many organic farmers, the possibilities for greater agency on their farms? being more independent of expert advice, of industrial inputs, of marketing boards and the like?is one of the main motivations for producing organically. In recent years, however, organic farming has moved increasingly into the mainstream and farm? ers find themselves facing the paradoxes of greater public recog? nition as well as greater government support and intervention.